Impacts of Downtown Developments to Facilitate Environmental Sustainability and Presence of Core and Frame: A Case Study of Saddar, Karachi, Pakistan - Tanveen A. Rasheed; M. Imran Akram; Azra Parveen Azad (Journal of Basic & Applied Sciences, 2018)
A real sustainable world and a livable environment for everyone is currently needed and becoming an extraordinarily challenging task. Sustainability for whom-who benefits and who loses? The increasing environmental problems are also hampering the sustainability. The remarkable increase in population and severe food shortages has brought unprecedented burden on land. Land is considered as space, territory, location, ecosystem, reserve and human habitat above all. Land-use provides a basis for identification of different functional zones in the city thus providing a framework for shaping the internal structure of a city. The best-planned development of any area is possible when the problems of that area are well understood, well documented and closely monitored. Systematic information on land-use / land cover classes, environmental problems and the available arrangement is critically important for future planning of an area. The rationale of this study is to indicate the presence of core and frame in the downtown area of Saddar, Karachi and to examine how finished downtown developments are designed to facilitate environmental sustainability. The field inventory has been conducted to find out the functional and physical developments and sustainability of the study area. In addition the process models have been applied to find out the environmental sustainability. The results of filed investigations show that Saddar does not fulfill the requirement of any of the classical land use models. With reference to the planned development of the core area, zoning laws should be applied to place the functions properly to their respective location. The main problems should be considered as prime matters for the city planners and agencies.